PEMBELAJARAN LITERASI DI SD NEGERI 1 PENATIH: SUATU TINJAUAN LITERATUR DAN IMPLIKASI PRAKTIS - Riva Prathiwi, Kadek Jayanthi; Trisna Dewi, Komang (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
This study aimed to describe the implementation of literacy learning at SDN 1 Penatih and identify strategies, obstacles, and the impact of the literacy program on the development of students' reading and writing competencies. This type of research was a qualitative descriptive study that focuses on the learning process, teacher-student interactions, and the implementation of the literacy curriculum in lower and upper grades. Research data were collected through classroom observations, in-depth interviews with class teachers, the school literacy coordinator, the principal, and several students, as well as document analysis such as lesson plans, literacy modules, reading journals, and student work. All data were analyzed using Miles & Huberman's analysis techniques, which include data reduction, data presentation, and thematic conclusion drawing. The results showed that SDN 1 Penatih has integrated literacy as a school culture through the School Literacy Movement (GLS) program with three main stages: habituation, development, and learning. Teachers use various strategies, such as read aloud, project-based literacy, class reading corners, and interactive digital media. The analysis results showed an increase in reading interest and text comprehension abilities in most students, especially in lower grades. However, several obstacles persist, such as limited availability of level-appropriate reading books, significant variation in student literacy skills, and limited digital literacy resources in some classrooms. The implications of this research indicated that successful literacy learning requires systematic school support through the provision of diverse reading materials, teacher training in literacy pedagogy, and collaboration between schools and parents in building a literacy environment at home. This study recommends strengthening technology-based literacy programs and improving the quality of formative literacy assessments to continuously monitor student development. Keywords: literacy, elementary school, learning, School Literacy Movement, SD Negeri 1 Penatih